Reduce Driveline Trauma Through Stabilization and Exit Site Management: 30 Days Feasibility Results from the Multicenter RESIST Study. Issue 3 (May 2016) - Stahovich, Marcia; Sundareswaran, Kartik S.; Fox, Sarah; Hallinan, William; Blood, Peggy; Chen, Leway; Pamboukian, Salpy V.; Chinn, Raymond; Farrar, David J.; Pagani, Francis D.; Blue, Laura
Abstract : The percutaneous lead management kit (PLMK) was developed for the HeartMate 2 (HM2) left ventricular assist device (LVAD) to reduce trauma at the exit site and to maintain a clean environment. REduce Driveline Trauma through StabIlization and Exit Site ManagemenT (RESIST) was a multicenter, prospective, nonrandomized study designed to evaluate the feasibility of the PLMK for managing the HM2 driveline exit site. Fifty patients were enrolled at five sites at a median of 495 days post-HM2 implant; 92% (46 of 50) of patients used the PLMK for a minimum of 30 days. At 30 days, more patients found the PLMK to be extremely comfortable (80% vs. 37%, p < 0.001) and extremely effective at stabilizing the driveline (82% vs. 40%, p < 0.001) compared with each center's standard of care. Frequency of dressing changes was 6–7 days or higher for 85% of the patients with PLMK. Three patients developed driveline infection while on PLMK (6%, 0.15 events per patient year), and 35 patients continued to use the PLMK after 6 months. The PLMK is easy to use, increases patient comfort, and increases driveline stability with a dressing change frequency of 6–7 days.